Versioning approach for data warehouse schema - Mat Yusof, Sharmila; Sidi, Fatimah; Affendey, Lilly Suriani; Ibrahim, Hamidah; Ishak, Iskandar; A. Jabar, Marzanah (Database Technologies and Applications Research Group (DbTA), Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2019)
A Data warehouse (DW) is a repository designed for querying and analyzing data. The main aims of a DW is to provide the most accurate and historically correct information to users to support the business analysis and decision-making. The input to DW is dependent on its business requirements and data sources. With the nature of dynamic business requirements and autonomous data sources, the requirement of the DW is inevitably changes over times. As the DW is very critical for organization’s business analysis and strategic decision-making, the dissemination of the changes is crucial to the DW system in order to supply a precise and reliable information. Thus, the objective of this paper is to present an approach to cater for DW change management problem. We apply the approach on TPC-H benchmark data to illustrate its practicality. The application shows that the proposed approach could assist designer to manage the DW schema changes.